Study of distribution and morphological characteristics of the trabecular bone in the uncinate process of the cervical spine using micro-computed tomography. - Yunteng Hao; Yuan Ma; Shaojie Zhang; Chaoqun Wang; Wei Wang; Xiaohe Li; Shang Gao; Kun Li; Jie Chen; Haiyan Wang; Yang Yang; Mingjie Gao; et al. (PLoS ONE)
The cervical uncinate process is a unique structure of the cervical spine that undergoes significant changes in its morphological characteristics with age, and these changes may be related to osteoporosis. This study aimed to observe the distribution of cancellous bone in the cervical uncinate process and its morphological features using micro-computed tomography (Micro-CT) to gain a deeper understanding of the morphological characteristics of the uncinate microstructure. We performed Micro-CT scans on 31 sets of C3-C7 vertebrae, a total of 155 intact bone samples, and subsequently used the measurement software with the Micro-CT system to obtain parameters related to the cancellous bone of the uncinate process. We found that the cancellous bone of the uncinate process was predominantly longitudinally cross-aligned and continuous with the cancellous bone within the vertebral body. Comparisons between the left and right sides of each parameter showed significant differences only in the bone surface area, and the peaks of each parameter were primarily concentrated in C4-C6. In this study, we found that the C5 uncinate process is the site of most significant stress in the cervical vertebrae, which leads to the earliest occurrence of osteoporosis, and this study provides experimental, theoretical bases for the prevention of cervical spondylosis and osteoporosis, and the diagnosis and treatment of related diseases.